A Novel Model of Venovenous Extracorporeal Membrane Oxygenation in Rats with Femoral Cannulation and Insights into Hemodynamic Changes - Edinger, Fabian; Zajonz, Thomas; Mayer, Nico; Schmidt, Götz; Schneck, Emmanuel; Sander, Michael; Koch, Christian; Justus Liebig University Giessen (My University, 2024)
The application of venovenous (VV) extracorporeal membrane oxygenation (ECMO) has gained wide acceptance for the treatment of acute severe respiratory failure. Since no rat model of VV ECMO therapy with femoral drainage has yet been described, although this cannulation strategy is commonly used in humans, this study aimed to establish such a model. Twenty male Lewis rats were randomly assigned to receive a sham procedure or VV ECMO therapy. After the inhalative induction of anesthesia, animals were intubated and the vascular accesses were placed surgically. While venous drainage was achieved through a modified multi-orifice 18 G cannula that was placed in the inferior vena cava through the femoral vein over a guide wire with an ultra-flexible tip, the venous return was realized via a shortened 20 G cannula into the jugular vein. Hemodynamic data were obtained from a tail artery and left ventricular pressure–volume catheter. Repetitive blood gas analyses were carried out, and systemic inflammation was measured using an enzyme-linked immunosorbent assay. While animals in the ECMO group showed adequate oxygenation and decarboxylation, there was no evidence of recirculation. VV ECMO therapy increased stroke volume (SV), cardiac output (CO), and left ventricular end-diastolic volume (LVEDV). ECMO-induced inflammation was reflected in increased levels of tumor necrosis factor alpha. However, no differences in interleukins 6 and 10 were seen. This study describes a frequently used cannulation strategy in humans for a rat model of VV ECMO. Despite successful oxygenation and decarboxylation, the oxygenated blood may reduce pulmonary vascular resistance and lead to an increased LVEDV, which is associated with increased SV and CO. This model allows us to answer research questions about topics such as intestinal microcirculation in further studies.
Keywords: ddc:610